Meropenem potentiation of aminoglycoside activity against Pseudomonas aeruginosa: involvement of the MexXY-OprM multidrug efflux system. (6th February 2018) - Poole, Keith; Gilmour, Christie; Farha, Maya A; Parkins, Michael D; Klinoski, Rachael; Brown, Eric D
Abstract: Objectives: To assess the ability of meropenem to potentiate aminoglycoside (AG) activity against laboratory and AG-resistant cystic fibrosis (CF) isolates of Pseudomonas aeruginosa and to elucidate its mechanism of action. Methods: AG resistance gene deletions were engineered into P. aeruginosa laboratory and CF isolates using standard gene replacement technology. Susceptibility to AGs ± meropenem (at ½ MIC) was assessed using a serial 2-fold dilution assay. mexXY expression and MexXY-OprM efflux activity were quantified using quantitative PCR and an ethidium bromide accumulation assay, respectively. Results: A screen for agents that rendered WT P. aeruginosa susceptible to a sub-MIC concentration of the AG paromomycin identified the carbapenem meropenem, which potentiated several additional AGs. Meropenem potentiation of AG activity was largely lost in a mutant lacking the MexXY-OprM multidrug efflux system, an indication that it was targeting this efflux system in enhancing P. aeruginosa susceptibility to AGs. Meropenem failed to block AG induction of mexXY expression or MexXY-OprM efflux activity, suggesting that it may be interfering with some MexXY-dependent process linked to AG susceptibility. Meropenem potentiated AG activity versus AG-resistant CF isolates, enhancing susceptibility to at least one AG in all isolates and susceptibility to all tested AGs in 50% of the isolates. Notably, meropenem potentiation of AG activity was linked to MexXY in some but not all CF isolates in which this was examined. Conclusions: Meropenem potentiates AG activity against laboratory and CF strains of P. aeruginosa, both dependent on and independent of MexXY, highlighting the complexity of AG resistance in this organism.